2018
DOI: 10.1007/s10072-017-3232-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of headache in juvenile myoclonic epilepsy: experience from a tertiary epilepsy center

Abstract: The comorbidity of headache and epilepsy is often seen in neurological practice. The objective of this study was to assess the prevalence, types of, and risk factors for headache in juvenile myoclonic epilepsy (JME). We assessed a total of 200 patients and 100 healthy controls in our study. Headache was classified in participants using a self-administered questionnaire. Demographical, clinical features and headache characteristics were recorded. Seizure and headache temporal profiles were noted. Headache was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…They highlighted the role of having a family history of migraine as a strong risk factor for migraine comorbidity, similarly 17 . In another cross‐sectional study, the migraine prevalence was found to be 23.5% in patients with JME, whereas it was 16% in the healthy controls 37 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They highlighted the role of having a family history of migraine as a strong risk factor for migraine comorbidity, similarly 17 . In another cross‐sectional study, the migraine prevalence was found to be 23.5% in patients with JME, whereas it was 16% in the healthy controls 37 …”
Section: Discussionmentioning
confidence: 97%
“…17 In another cross-sectional study, the migraine prevalence was found to be 23.5% in patients with JME, whereas it was 16% in the healthy controls. 37 A plausible explanation for this close relationship between JME and migraine may be through common genetic traits. The coexistence of alterations in the genes encoding ion channel proteins such as CACNA1A, ATP1A2, SCN1A, and PRRT2 in familial hemiplegic migraine and genetic epilepsies have been extensively documented before.…”
Section: F I G U R Ementioning
confidence: 99%
“…For instance, a review conducted to see the relationship between headache and epilepsy reported the comorbidity of headache and epilepsy as a result of common genetic mutations and clinical features [18,19], but the suggested link is not revealed conclusive evidence of a real causal association [20]. Further, studies also suggested that there are genetic relationships [19] as well as common underlying pathophysiological mechanisms including the imbalance between excitatory and inhibitory neurotransmitters in epilepsy and headache, especially for migraine [18,21]. Proposed theories for shared etiologies include ion channel dysfunction, glutamatergic mechanisms, and mitochondrial dysfunction [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, estimating the burden of headaches among patients with epilepsy is critically important. Even though a systematic review and meta-analysis has been conducted in 2017 on a similar area of study [27], however, it only assessed the comorbid relationship between migraine and epilepsy [21]. In spite of that, the current review tried to investigate the pooled prevalence of headaches such as migraine, tension-type headaches, and others among patients with epilepsy to summarize the available epidemiologic evidence on the topic and formulate recommendations for future research as well as clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile myoclonic epilepsy has both a monogenetic and a complex genetic origin. In one study, 70% of people with this form of epilepsy reported a family history of migraine, almost twice as many as in an age-matched and sex-matched control group, suggesting an overlap in genetic risk between juvenile myoclonic epilepsy and migraine 144 . Some specific genes have also been associated with both epilepsy and migraine 66,145 .…”
Section: [H1] Overlapping Geneticsmentioning
confidence: 99%